DEBT TO EQUITY RATIO, CASH RATIO, TOTAL ASSET TURNOVER DALAM MEMPENGARUHI RETURN ON ASSETS SERTA DAMPAKNYA BAGI NILAI PERUSAHAAN MAKANAN DAN MINUMAN TBK DI BEI TAHUN 2020-2023 - Wahyuni, Ayu Sri; Pramitasari, Triska Dewi; Nanggala, Ardhya Yudistira Adi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the effect of the debt to equity ratio, cash ratio, and total asset turnover on return on assets and their impact on the value of food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2020–2023. The research method used is a quantitative approach. The sampling technique employed was purposive sampling, resulting in nine companies selected as samples out of a total population of twentysix. The data used are secondary data in the form of annual financial reports published on the official website www.idx.co.id. Data analysis was conducted using the Partial Least Squares (PLS) analysis technique with SmartPLS version 3.0 software. Based on the PLS test, the results show that the debt to equity ratio has a negative and insignificant effect on return on assets; the cash ratio has a positive and insignificant effect on return on assets; and the total asset turnover has a negative and insignificant effect on return on assets. The debt to equity ratio has a negative and insignificant effect on firm value. the cash ratio has a negative and insignificant effect on firm value. The total asset turnover has a positive and significant effect on firm value. Return on Assets has a positive and insignificant effect on firm value. The debt to equity ratio has a positive and insignificant effect on firm value through return on assets. The cash ratio has a negative and insignificant effect on firm value through return on assets. The total asset turnover has a negative and insignificant effect on firm value through return on assets.